Marketing Analysis of Bird’s Chili in Kehiran Village East Sentani District Jayapura Regency - Maga, La; Rusianti, Anita; Iwo, Lidiah Tereda; Sepang, Secilia Vanesa; Waroi, Heldo Mariche; Senik, Demas (JURNAL AGRIBISAINS, 2026)
The length of the marketing channel will determine farmers’ profitability, resulting in high marketing margins at the trader level, low prices received by farmers (farmer’s share), and high accumulated marketing costs. This also leads to low marketing efficiency. The purpose of this study is to analyze the marketing of cayenne pepper which includes: marketing channels; marketing margin, total margin, and marketing profit; farmer share; and marketing efficiency. This research was conducted in Kehiran Village, East Sentani District, Jayapura Regency. The data used in the study is quantitative data, obtained through interviews with 20 cayenne pepper farmers, 2 respondents with wholesalers, 3 respondents with collectors, and 5 respondents with retailers. Data analysis in this study uses a quantitative descriptive approach. Based on the analysis results, cayenne pepper marketing consists of three marketing channels. Marketing channel III has the highest total margin, because it consists of three marketing institutions: collectors, wholesalers, and retailers. The highest farmer share occurred in marketing channel I, at 63.64%, as farmers sell their harvest directly to retailers. Marketing channels I, II, and III are still considered efficient, with efficiency values ​​<50%. However, the longer the marketing channel, the higher the marketing costs of cayenne pepper in Kehiran Village. In marketing activities, the government should establish a farming cooperative to accommodate farmers’ harvests. Furthermore, the cooperative will play a role in distributing agricultural products to retailers in Sentani City. This is done to improve the marketing efficiency of agricultural products, especially cayenne pepper.